Typology of the social learning process of ornamental plant farmers using social media for e-commerce in Bogor Regency - Nurfathiyah, Pera (JALOW | Journal of Agribusiness and Local Wisdom, 2023)
The advancement of information and communication technology (ICT) has created a digital literacy gap among ornamental plant farmers, particularly in utilizing technology to increase income by expanding access to market knowledge and information. This study aims to identify the typology of ornamental plant farmers based on their behavior in using social media for e-commerce. The findings of this study are intended to provide recommendations on which stages of the social learning process need to be improved to address the digital literacy gap among ornamental plant farmers. This research employs a survey method using questionnaires and qualitative data to support and explain the findings. Data collection was conducted using a simple random sampling method, resulting in a sample of 210 ornamental plant farmers in Bogor Regency. The data were analyzed using an index score, where the scores from direct social media pathways and socially mediated of social media use for e-commerce were converted into a scale of 0 to 100. The scoring categories were: < 50 (low), > 50–75 (moderate), and > 75 (high). The results indicate that the typology of farmers based on direct social media usage and socially mediated pathway into the third type, where their behavior in using social media for e-commerce is high, but their use of direct social media pathways and social media system pathways is low. These farmers are in the learning stage of reproducing results from observations and suggests that farmers have a relatively good ability to utilize social media for e-commerce activities.